2002
DOI: 10.1051/animres:2002025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding a mixture of malate and yeast culture (Saccharomyces cerevisiae) on milk production of Murciano-Granadina dairy goats

Abstract: -Twenty-four Murciano-Granadina dairy goats were used to investigate the effects of supplementation with a mixture of malate and yeast (Saccharomyces cerevisiae) on milk production. The goats were machine milked once a day after parturition and were assigned to two balanced groups on week 4 of lactation. The experimental groups were kept separately in pens and were fed a daily diet based on a dehydrated forage mixture (alfalfa hay: maize whole plant, 1:1) ad libitum, 0.3 kg alfalfa pellets and 0.2 kg barley gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…In agreement with our study, some authors have reported reductions in feed intake (Wallace et al, 2006;Molano et al, 2008). However, other authors have found no effect on intake (Kung et al, 1982;Martin et al, 1999;Montano et al, 1999;Salama et al, 2002;Carro et al, 2006, McCourt et al, 2008. It should be noted that in the case of McCourt et al (2008), who offered up to 11% of DMI as FA, the FA was encapsulated.…”
Section: Feed Intake and Digestibilitysupporting
confidence: 92%
“…In agreement with our study, some authors have reported reductions in feed intake (Wallace et al, 2006;Molano et al, 2008). However, other authors have found no effect on intake (Kung et al, 1982;Martin et al, 1999;Montano et al, 1999;Salama et al, 2002;Carro et al, 2006, McCourt et al, 2008. It should be noted that in the case of McCourt et al (2008), who offered up to 11% of DMI as FA, the FA was encapsulated.…”
Section: Feed Intake and Digestibilitysupporting
confidence: 92%
“…Goats supplemented with yeast probiotics show improvements in milk production but the results are quite variable [15][16][17][18][19][20]. These studies indicated that stronger responses to prebiotic or probiotic treatments were achieved with animals that were challenged by multiple factors such as heat [45] and feed quality [17].…”
Section: Discussionmentioning
confidence: 99%
“…In monogastric livestock, probiotic and prebiotic feed additives mitigate pathogen issues in a number of ways including establishing beneficial bacteria in the intestinal tract [8,9], improving the ability of the mucosa to withstand infection [10,11,12], improving the defense system [8,9], binding toxins [3,4,13] and interfering with pathogen colonization sites [3,4,14]. Probiotics can improve milk production and rumen function in goats [15][16][17][18][19][20][21] with a 280-head commercial dairy herd were used in the study. The goats were housed in an open stall barn with ventilation and had continuous access to water.…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of milk yield after the peak of lactation was greater in cows receiving a yeast supplement than in the cows of the control group (Strzetelski et al, 1996). However, the results on the use of S. cerevisiae in dairy cows (Dann et al, 2000) and dairy goats (Salama et al, 2002) are also contradictory. Dietary factors such as forage-toconcentrate ratio and forage type are important in determining the response to malate and yeast culture supplementation (Piva et al, 1993), which may explain the contradiction found in the results of the previous studies.…”
Section: Introductionmentioning
confidence: 98%